ANALISIS KETERSEDIAAN TENAGA KESEHATAN SERTA STANDAR PROFESI STAFF DI UPT PUSKESMAS PARGARUTAN KECAMATAN ANGKOLA TIMUR KABUPATEN TAPANULI SELATAN - Ade Fitri Arianti; Bunga Elvyan Br. Damanik; Istikhoma Rambe; Rehana Nugraha B.Sitorus; Quen Kholisa Purba; Fitriani Pramita Gurning (Lembaga Pengembangan Kinerja Dosen, 2023)
Puskesmas as a provider of basic health services has a very important role in maintaining public health. If it functions properly, the puskesmas will be able to provide quality services for people in need. The success of puskesmas in carrying out their programs is determined by the availability of human resources (HR) that are balanced between medical personnel on one side and promotive and preventive personnel on the other. The relationship between ability, workload, work discipline, and work motivation with the performance of health workers is obtained that there is a relationship between ability, workload, work discipline, and work motivation with the performance of health workers. Research Objectives: The purpose of this study is to analyze the suitability of the main tasks and functions (tupoksi) with education and skills as well as means of supporting work. Research Methods: The author of this article uses a descriptive qualitative method that seeks to describe an object or subject of an inductive nature. Result: Inappropriate tupoksi due to limited health workers in puskesmas, especially limited skills based on the type of education. As a result, there are health workers who are in charge of programs that do not match their skills. Conclusion: The lack of health workers makes the tupoksi incompatible with the educational background of the staff in charge of the program at the Puskesmas.